2011
DOI: 10.1007/978-1-4419-6108-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Task-Technology Fit Theory: A Survey and Synopsis of the Literature

Abstract: Over the past decade there has been a notable increase in the use of Task-Technology Fit (TTF) theory within the field of information systems. This theory argues that information system use and performance benefits are attained when an information system is well-suited to the tasks that must be performed. As such, it seeks to offer an account of two of the key outcomes of interest to information systems (IS) researchers. Continued interest in the application of TTF theory is therefore expected and, as a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 80 publications
1
44
0
Order By: Relevance
“…TTF provides a means to quantify the effectiveness of technology in an organizations [6]. In 2012, Furneaux [7] identified the "notable increase in the use of TTF theory". This trend has continued over the years, with both an increase in the yearly number of documents published as well as in the range of environments which the theory is used, as discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TTF provides a means to quantify the effectiveness of technology in an organizations [6]. In 2012, Furneaux [7] identified the "notable increase in the use of TTF theory". This trend has continued over the years, with both an increase in the yearly number of documents published as well as in the range of environments which the theory is used, as discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the wide use of the theory, only two publications by Cane and McCarthy [8] and the work by Furneaux [7] was found that summarizes and synthesizes TTF related studies. The article by Cane and McCarthy [8] is limited to a small number of studies, all of which were conducted before 2006, and only considered how the studies defined TTF and its surrounding components.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the extent to which a PSS supports planning tasks is in this literature conceived as the so-called task-technology fit (Goodhue and Thompson 1995). Whereas several definitions exist for tasktechnology fit (see Furneaux 2012 for an overview), the one arguably most suited for the PSS debate reads: 'The matching of the functional capability of available information technology with the activity demands of the task at hand' (Dishaw and Strong 1998, p. 154). In the PSS debate, the notion of task-technology fit has received relatively little attention.…”
Section: Conceptual Framework: Task-technology Fitmentioning
confidence: 99%
“…Furneaux (2012) summarises the outcomes of TTF as described in MIS and GSS research. A range of possible outcomes are discerned, including the quality of the decision or solution and the attitude about the technology and the intention to use it.…”
Section: Conceptual Framework: Task-technology Fitmentioning
confidence: 99%
See 1 more Smart Citation